Financial policy for shaping the optimal corporate capital structure - S.M.; N.G.; V.V. (Економіка, управління та адміністрування)
The paper carries out the content analysis of scientific publications devoted to the management of financial structure of corporate capital on the basis of research, the results of which were published both in domestic scientific journals and in Scopus scientometric database. For the study, not only analytical calculations obtained from Scopus were used, but also bibliometric maps built on the basis of the formed sample using VOSviewer 1.6.16 and Google Books Ngram Viewer. The results of the study showed that the financial policy of an enterprise should be considered as the goal of financial management determined by the owners and agreed with the management, which provides for the development of an algorithm of actions aimed at forming an optimal capital structure, the choice of forms and methods for achieving it both in the short and long term. At the same time, a high-quality financial policy should comply with the following key principles: fairness, compliance with current legislation, feasibility, accessibility, and risk level, which corresponds to the level of the corresponding risk of both the owners and the management of a company.